1998
DOI: 10.1080/10715769800300341
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of antioxidants against UVA-induced DNA damage in human skin fibroblasts in culture

Abstract: Ultraviolet A radiation (UVA, 320-400 nm) is mutagenic and induces genomic damage to skin cells. N-acetyl-cysteine (NAC), selenium and zinc have been shown to have antioxidant properties and to exhibit protective effects against UVA cytotoxicity. The present work attempts to delineate the effect of these compounds on genomic integrity of human skin fibroblasts exposed to UVA radiation using the single cell gel electrophoresis (SCGE) or Comet assay. The cells were incubated with NAC (5 mM), sodium selenite (0.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 31 publications
3
33
0
2
Order By: Relevance
“…It has been proposed that the beneficial effect of NAC mainly comes from its capability of directly scavenging Å OH radicals as well as its function as a glutathione precursor [12][13][14][15][16][17]. However, there are still considerable controversies regarding the antioxidant efficacy of NAC.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that the beneficial effect of NAC mainly comes from its capability of directly scavenging Å OH radicals as well as its function as a glutathione precursor [12][13][14][15][16][17]. However, there are still considerable controversies regarding the antioxidant efficacy of NAC.…”
Section: Introductionmentioning
confidence: 99%
“…First, to investigate the effect of CSE with regard to protecting against H 2 O 2 -induced cell toxicity, we measured cell viability using the MTT assay. NAC, a dietary supplement commonly used as an antioxidative and skin-protecting agent, was used as a positive control [20] . The results showed that treatment with CSE at 20-500 g/ml or NAC at 2 m M alone showed no effect on the cells ( fig.…”
Section: Resultsmentioning
confidence: 99%
“…232 Moreover, NAC has been shown to have antioxidant properties against UVA cytotoxicity in human fibroblasts. 208 The mechanism of action is still not known; however, it has been reported that the photoprotective effect of NAC and glutathione ethylester did not correlate to GSH levels. 233 UVB can induce immunosuppression by generating damage to DNA.…”
Section: Other Photoprotective Agentsmentioning
confidence: 98%
“…207 Zinc supplementation protects against UVA-induced DNA damage in human skin fibroblasts. [208][209][210] Divalent zinc ion, topical form of zinc, has been shown to provide antioxidant photoprotection for skin by two mechanisms; zinc ions may replace redox active molecules, such as iron and copper; alternatively, it may induce the synthesis of MTs, sulhydryl-rich proteins that protect against free radical. 211,212 It has been shown to protect mouse skin again UVA-and UVB-induced sunburn cell formation.…”
Section: Other Photoprotective Agentsmentioning
confidence: 99%